The Water Content, Solubility, and Optical Properties of Whey-Gelatin Multilayer Films Enriched with Green Tea Powder - Fahrullah Fahrullah; Bulkaini Bulkaini; Djoko Kisworo; Wahid Yiulianto; Baiq Rani Dewi Wulandani; Haryanto Haryanto (Jurnal Biologi Tropis, 2023)
This biodegradable packaging is designed to reduce the negative impact on the environment caused by plastic pollution, while still maintaining the shelf life, quality and safety of the packaged food products. The objective of this study was to analyse the moisture content, solubility and optical properties of whey-gelatin multilayer film enriched with green tea powder. This study was conducted experimentally, using a completely randomised design with four treatments and five replicates. The treatments consisted of P1: gelatin/whey-gelatin (G/WG); P2: gelatin/5% green tea powder/whey-gelatin (G/5% GTP/WG); P3: gelatin/10% green tea powder/ whey-gelatin (G/10% GTP/WG) and P4: gelatin/15% green tea powder/whey-gelatin (G/15% GTP/WG). The moisture content and solubility values of whey-gelatin multilayer films showed significant differences (P<0.01). Moisture content was 33.0204-35.3653%; solubility was 40.19-49.96%. The film enriched with 5% green tea powder (P2) produced the best values of moisture content of 34.3536%, solubility of 47.97% and optical (L*= 61.00; a*= -0.36 and b*= 22.58).